2003
DOI: 10.1046/j.1540-8167.2003.01554.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Implantable Cardioverter Defibrillator Therapy in the Antiarrhythmics Versus Implantable Defibrillators (AVID) Trial

Abstract: Delivery of ICD therapy in AVID patients was common, primarily due to VT. Inappropriate ICD therapy occurred frequently. Use of ICD therapy as a surrogate endpoint for death in clinical trials should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(112 citation statements)
references
References 37 publications
5
102
3
2
Order By: Relevance
“…The initial generations of ICDs did not record and save electrograms (EGMs), leading to a reduced appreciation for the frequency and impact of inappropriate shocks. With the advent and then dominance of primary prevention indications, avoidable shocks assumed a relatively larger proportion of total therapy [78][79][80][81][82][83]. Gradually, publications have increased awareness of the frequency and the diverse range of adverse outcomes associated with avoidable ICD therapy, and have demonstrated that avoidable ICD shocks can be reduced by evidence-based programming of the detection rate, detection duration, antitachycardia pacing (ATP), algorithms that discriminate supraventricular tachycardia (SVT) from VT, and specific programming to minimize the sensing of noise [81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Tachycardia Detection Programmingmentioning
confidence: 99%
“…The initial generations of ICDs did not record and save electrograms (EGMs), leading to a reduced appreciation for the frequency and impact of inappropriate shocks. With the advent and then dominance of primary prevention indications, avoidable shocks assumed a relatively larger proportion of total therapy [78][79][80][81][82][83]. Gradually, publications have increased awareness of the frequency and the diverse range of adverse outcomes associated with avoidable ICD therapy, and have demonstrated that avoidable ICD shocks can be reduced by evidence-based programming of the detection rate, detection duration, antitachycardia pacing (ATP), algorithms that discriminate supraventricular tachycardia (SVT) from VT, and specific programming to minimize the sensing of noise [81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Tachycardia Detection Programmingmentioning
confidence: 99%
“…As reported previously [11], ICD therapy cannot be used as a surrogate marker for mortality in clinical trials involving secondary population. …”
Section: Limitationsmentioning
confidence: 89%
“…Arrhythmic death constituted less than 1 percent of all ICD episodes 11 . On multivariate analysis, the relative risk of all cause mortality (HR, 95% C.I, p) associated with an appropriate (1.06, 0.38 to 1.48, NS) or an inappropriate shock (1.63, 0.48 to 5.46, NS) did not differ significantly from that in patients who have not received any shocks (Table 3).…”
Section: Impact Of Icd Shocks On Outcomesmentioning
confidence: 98%
See 1 more Smart Citation
“…Lots of studies demonstrated that ATP terminates most of VTs but with a 1% to 7% risk of acceleration or precipitation of these arrhythmias [1,2]. Also, anti-bradycardia therapy can have an intrinsic arrythmogenic risk [3].…”
Section: Introductionmentioning
confidence: 99%